Emissions trading and profit-neutral grandfathering - Hepburn, C; Quah, J; Ritz, R (University of Oxford, 2006)
This paper examines the amount of grandfathering needed for an emissions trading scheme (ETS) to have a neutral impact on firm profits. We provide a simple formula to calculate profit-neutral grandfathering in a Cournot model with firms of different sizes and a general demand function. Using this formula, we obtain estimates of profit-neutral grandfathering for the electricity, cement, newsprint and steel industries. Under the current EU ETS, firms obtain close to full grandfathering; we show that while this may still leave some firms worse off, others have probably benefitted substantially. We find no evidence that any industry as a whole could be worse off with full grandfathering. We also show that the common presumption that a higher rate of cost pass-through lowers profit-neutral grandfathering is unreliable